Relaciones entre la capacidad de repetir sprints, el salto vertical y la fuerza de miembros superiores en jugadores profesionales de baloncesto - Balsalobre-Fernandez, C.; Tejero Gonzalez, C. M.; del Campo-Vecino, J.; Bachero Mena, B.; Sanchez Martinez, J. (Archivos de medicina del deporte, 2014)
The repeated sprint ability (RSA), counter-movement jump (CMJ) performance and upper-body strength are very important variables in high-level basketball competition. However, the relationships among these variables are poorly studied in elite basketball players. Thus, the purpose of this research is to study the relationships among the Running-Based Anaerobic Speed Test (RAST ), the CMJ and upper-body strength in professional male basketball players from the highest-level competition of Spain (League Endesa). Eleven, athletes (N=11, age = 24.5 ± 5.8 yrs, height = 200 ± 10.9 cm, weight = 98.4 ± 9 kg) were tested on the RAST, the CMJ before and after the RAST and the bench press strength in one single morning. The results show, high and statistically signifi cant correlations between the RAST fatigue index (FI) and CMJ loss (the diff erence between pre and post RAST measures) (r = 0.78, p <0.01), the FI and the maximum force production on the bench press (r = -0.86, p <0.01), and the CMJ loss and the load at which peak power is produced on the bench press (r = -0.77, p <0.01). Our data highlights the remarkable relationship among repeated-sprint ability, the CMJ and upper-body strength in professional male basketball players. For this, it seems clear that elite basketball players may benefi t from training programs designed to improve such variables simultaneously. This may be relevant for the strength & conditioning training of such athletes.